Road culture : an investigation of the road as a means of mental and physical exploration - Meistre, Brent Arthur (Rhodes University, Faculty of Humanities, Department of Fine Art, 2000)
Chapter one considers various manifestations of the concept of 'journey' and how they have changed over history. The Odyssean journey that the hero undertakes to reach a point of self-realisation is investigated. This leads to a other discussion of types of journeys such as pilgrimages, as well as 'wandering'. These are contrasted with the twentieth century perceptions of journey. Questions of travel are then dealt with: how the nature of the traveller's path has changed over the centuries, various points of travel and gender, and how in the last century solitary travel has been transformed into mass tourism. The second chapter deals specifically with the motorcar, the mobility it enables and how it has led to the rise of a roadside culture. Different factors that influenced the rise of the motorcar are looked at. The motorcar as a cell and eroticism and the car are also investigated. The twentieth century city, it's restructuring, as well as the highway systems is discussed. In Chapter Three, the sense of freedom that the motorcar created is considered in particular reference to escape, aimlessness, and road weariness, as well as the landscape as a symbol of freedom. This leads to a discussion on the notion of speed, the sense of power and the romanticisation of death in car crashes. Chapter Four investigates masculinity and the road. The frontier as a place in the psyche of the male is also dealt with. The road as a means of testing and regaining masculinity in the mid-twentieth century is considered. Issues of the male domination of the land and the feminine are discussed, with the chapter ending with a brief examination of the woman as traveller. Lastly the masters' submission exhibition, entitled RODE is discussed with direct reference to the theories investigated in the previous chapters. Individual works as well as the methodology are looked at closely.
Keywords: Roads in art; Travel in art; Travel -- Psychological aspects; Travelers -- Psychology